KESEJAHTERAAN KELUARGA PESERTA DAN BUKAN PESERTA PROGRAM GERAKAN PEREMPUAN UNTUK OPTIMALISASI PEKARANGAN (GPOP) - Riza, Riza; Hartoyo, Hartoyo; Muflikhati, Istiqlaliyah (Jurnal Ilmu Keluarga dan Konsumen, 2014)
Program of Women’s Movement for Home garden Optimization (GPOP) was one of the government's efforts to encourage families to manage home garden optimally in order to improve the family well-being. This program wasconducted since 2011 by Ministry of Agriculture. The aim of this research was to analyze the well-being of GPOP participant’s family and nonparticipant’s family in Depok City, West Java Province; and to analyze the factors that influenced the well-being. This research involved 60 GPOP participants’ family and 60 nonparticipant’s family that chosen by random sampling. Family well-being measured by using objective indicator based on poverty line according to BPS and subjective indicator based on assessment of wive on various aspects of her family well-being. This study found that even families who did not become participants of GPOP had higher achievement of optimization of the home garden than participants. The results showed that most familyies, both participants and nonparticipants, had been prosperous according to the measurement of two indicator, objective and subjectife assessment. However, the level of the family well-being of participants was higher than nonparticipants. Moreover, family’s well-being was affected by the amount of family assets, but it was not influenced by membership of GPOP.